2016
DOI: 10.1590/1678-457x.0049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of nutraceutical capsule waste of safflower oil in the mechanical characteristics of corn starch films

Abstract: Biodegradable films blends made of safflower oil nutraceutical capsules waste: corn starch (20:4, 30:4, 40:4 and 50:4) were prepared. The objective of this study was to evaluate the influence of addition of different concentrations of safflower oil nutraceutical capsule waste in the mechanical properties (tensile strength, elongation at break, Young's modulus) and thickness of corn starch films. A decrease in tensile strength and Young's modulus and an increase in elongation at break were observed with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
2
6
1
1
Order By: Relevance
“…The Young's modulus is a parameter that has a direct relationship with film stiffness. The Young's modulus results were similar to those reported by [56], where a reduction in corn films occurred with the addition of safflower oil encapsulate.…”
Section: Mechanical Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…The Young's modulus is a parameter that has a direct relationship with film stiffness. The Young's modulus results were similar to those reported by [56], where a reduction in corn films occurred with the addition of safflower oil encapsulate.…”
Section: Mechanical Propertiessupporting
confidence: 87%
“…The higher the concentration of the nanoemulsion added to the gelatine film, the higher the energy needed to break its stability, since, by exerting plasticizing action, it did not allow protein chains to interact with each other. Authors such as those of [55][56][57][58][59] observed similar behavior when using protein as a surfactant to achieve the incorporation of oil in gelatine films. The addition of nanoemulsion to the gelatine films had a positive effect because there was less interaction between proteins, making the films more stable.…”
Section: Thermal Properties and Fourier Transform Infrared (Ftir)mentioning
confidence: 78%
“…The results in Young's modulus are similar to those reported byde Campo et al (2016), where a reduction in this parameter in corn films occurred with the addition of safflower oil encapsulate. The results of the elongation percentage were similar to those reported by…”
supporting
confidence: 89%
“…TS was lower in our product than in films obtained from fruit residues (Farias et al, 2012) and higher than reported for edible starch films with added safflower (Campo et al, 2016). This low TS was explained by conformational changes in the molecular structure of the dehydrated product, formed by the plastifying effect of water used in the formulation (Cuq et al, 2011).…”
Section: Resultscontrasting
confidence: 57%